Current progress and future perspective of super-enhancers: a viable and effective bridge between the transcriptional apparatus and disease - Wang, Ran; Li, Aiying; Pang, Zongran (Frontiers in Genetics, 2025)
Super-enhancers are a super-cluster of enhancers formed by serially arranged regulatory elements that can strongly drive the expression of cell-related genes. Hundreds of SEs in cells affect cell identity and fate-determining processes. Previous studies have verified that the expression of pathogenic genes is highly correlated with the abnormal activation of SEs in malignant tumorigenesis, dementia, diabetes, and many autoimmune diseases. Also, enhancer RNAs (eRNAs) can be regarded as crucial markers for SEs. Here, we summarize the discovery process and basic concepts of SEs, describe the structural characteristics and functional regulation of SEs in different tumor diseases, Alzheimer’s disease, and immune-related diseases, with a focus on typical diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis. In this review, we also discuss the potential clinical applications of SE, as well as the research prospects in this field.